Bacterial Endo-Symbiont Inhabiting Tridax procumbens L. and Their Antimicrobial Potential. (23rd November 2015) - Baker, Syed; Kavitha, Kumara Shanthamma; Yashavantha Rao, Huvinakola Chinnappa; Rakshith, Devaraju; Harini, Ballagere Puttaraju; Kumar, Komal; Satish, Sreedharamurthy
Abstract : Bacterial symbionts inhabiting Tridax procumbens L. were screened for antimicrobial potential with the aim to isolate potent bacteria bearing significant activity against test pathogens. The selected isolate was subjected to large scale fermentation to extract antimicrobial metabolite. The organic phase was reduced under vacuum pressure and crude ethyl acetate extract (10 mg/mL) was evaluated for antimicrobial activity against panel of test pathogens. The antibacterial activity was measured as a zone of inhibition and compared with standard antibiotics, gentamicin and tetracycline. Similarly, antifungal activity was compared with miconazole and bavistin. Significant activity was conferred against Shigella flexneri (MTCC 731) with27 ± 1.5 mm zone across the disc. Partially, purification of antimicrobial metabolite with TLC-bioautography and HPLC resulted in active fraction bearing activity atR f 0.65 and eluting between 4 and 5 retention times. The obtained results are promising enough for future purification and characterization of antimicrobial metabolite. Thus, the study attributes to the growing knowledge on endophytes as one of the rich sources of antimicrobial potentials.